Foreword - Mwombeki, Fidon R. (Complexities of Theologies of Wealth and Prosperity: Africa in Focus, 2022)
Since 2019, the All Africa Conference of Churches (AACC) started the implementation of its 2019-2023 strategy. One of the thematic areas for Theology, Interfaith Relations and Ecclesial Leadership Development programme is “Addressing Misleading Theologies.” It is from that perspective that AACC engages church leaders in identifying, analysing and deconstructing misleading theologies in the continent, to counter their destructive effects on the population
free